2003
DOI: 10.1021/jp036386s
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of the Reactions of BH2+ with H2, Methane, Ethane, Ethylene, and Acetylene in the Gas Phase

Abstract: We have studied the potential energy surface for the reactions of BH 2 + with H 2 , methane, ethylene and acetylene at the CCSD(T)/cc-pVTZ//MP2(full)/cc-pVTZ level and the reaction of BH 2 + with ethane at the CCSD(T)/ 6-311G(d,p)//MP2(full)/6-311G(d,p) level of theory. A complete survey of the potential energy surfaces is presented and the structures of the stationary points and the mechanisms of these reactions are discussed. The calculations suggest that the products of these reactions are formed by additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…22 It has also been observed with other electrophiles, such as in the reaction of BH 2 + with CH 4 and C 2 H 6 . 23,24 In addition to CH 2 I + , Mayhew et al also observed CH 3 I + although with a small branching ratio (14%). 19 We do not observe this reaction channel unless the helium flow in the reaction flow tube is reduced considerably; only under these conditions is a small but noticeable peak corresponding to CH 3 I + observed.…”
Section: Resultsmentioning
confidence: 99%
“…22 It has also been observed with other electrophiles, such as in the reaction of BH 2 + with CH 4 and C 2 H 6 . 23,24 In addition to CH 2 I + , Mayhew et al also observed CH 3 I + although with a small branching ratio (14%). 19 We do not observe this reaction channel unless the helium flow in the reaction flow tube is reduced considerably; only under these conditions is a small but noticeable peak corresponding to CH 3 I + observed.…”
Section: Resultsmentioning
confidence: 99%
“…The reactivities of ethylene and acetylene have been demonstrated to be quite similar in many different types of reactions. Quantum chemical calculations have been used to compare the relative reactivities in, for example, cycloaddition, , phosphinidene addition, sulfur addition, borohydride cation addition, hydration on zeolite, and ylidic radical addition . The barriers for these reactions were found to be rather close between ethylene and acetylene, with the largest difference on the order of 4 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…Related hypervalent species may be involved in high temperature hydrogen transfer reactions catalyzed by trialkyl boranes, the recent hydrogen activation experiments of Stephan et al and related studies, and gas phase equilibria involving BH 2 (+), H 2 , and BH 4 (+) . The relationship between 38 and 16a has a close parallel in the cationic ammonia borane derivatives [H 3 N•BH 4 ] + (borenium ion hydrogen adduct) and [H 3 N•BH 2 ] + (borenium ion), structures that have been evaluated computationally …”
Section: Discussion; Evaluation Of Potential Reactive Intermediatesmentioning
confidence: 99%